PEMETAAN DAERAH RAWAN KEKERINGAN DI BALI-NUSA TENGGARA DAN HUBUNGANNYA DENGAN ENSO 2) MENGGUNAKAN APLIKASI DATA PENGINDERAAN JAUH - I Wayan Nuarsa; I Wayan Sandi Adnyana; Abd. Rahman As-syakur (Bumi Lestari Journal of Environment, 2015)
In this study, the use of SPI (Standardized Precipitation Index) combined with remote sensingdata is performed to map vulnerable drought areas in Bali-Nusa Tenggara regions. Analysisalso carried out to find the relationship between Vulnerable drought areas in Bali-NusaTenggara with El Niño phenomena. Bali-Nusa Tenggara islands are a chain of islands thathas a semi-arid climate type and resulted vulnerable to meteorological drought. Therefore,mapping of vulnerable drought areas in the region necessary to be carried out. The spatialpattern of the annual average value of SPI-6 in Bali Nusa Tenggara areas in 1998-2010indicates the spatial distribution follows the ENSO events. It also indicated in the spatialpattern relationship between ENSO and SPI in Bali-Nusa Tenggara islands. This studyindicates that remote sensing data such as TRMM 3B43 has the capability to be used as adata source to analyze the spatial patterns of vulnerable drought areas, particularly in theBali-Nusa Tenggara Islands. In addition, the TRMM data also possible to be used as a datasource to analyze the vulnerable drought areas in other parts of Indonesia.